Simulation on the interaction between particles and fields for gyroklystron amplifier - Guo, Jianhua; Li, Xiang; Yu, Sheng; Li, Hongfu (Compel, 2012)
Purpose - The purpose of this paper is to formulate and simulate the interaction between particles and fields for gyroklystron amplifier rapidly and effectively.Design methodology approach - From Maxwell's equations, transient electromagnetic field equations and particle motion equations, as the subject of a self-consistent field theory, are obtained by semi-analytical and semi-numerical method. A numerical calculation model on the interaction between particles and fields is proposed and illustrated in detail. Based on above-mentioned field theory, calculation model and the Runge-Kutta method, a program to simulate the interaction between particles and fields is designed and its software implementation is achieved using Fortran language. To testify the correctness of the calculation model, a millimeter wave gyroklystron amplifier is simulated by the program, and some numerical results are presented and analyzed. Meanwhile, a contrast among the simulated frequency characteristic, the FDTD-PIC results and the experiments is made. The computing resources needed by the program are compared with that needed by the FDTD-PIC method.Findings - The calculation results show that the model and the program take less CPU time and fewer computing resources than FDTD-PIC simulation. Moreover, simulated results are in accord with the FDTD-PIC results and the experiments.Originality value - A calculation model on the interaction between particles and fields is proposed and achieved in this paper. A program is designed and proved to be a fast and effective calculation tool for solving the simulation of the interaction. In addition, a detailed speed spread model of particles is studied. The calculation model considering speed spread, the program and the simulated results constitute the main contribution of this paper.